Focus on coal power station installations and population health - Marco Valenti; Francesco Masedu; Sergio Tiberti (Istituto Superiore di Sanità, 2011)
Damage to health associated with emissions from coal power stations can vary greatly from one location to another depending on the size of the plant, location and the characteristics of the population. Population-based studies conducted by independent groups in different locations around the world show effects on health in populations at higher risk, but failed to definitely demonstrate direct effects on morbidity and mortality, to be exclusively attributed to the presence of active power stations. However, evidence on the role of micropollutants from power station activities suggests that a complete and thorough analysis should be made on the environmental cycle. Therefore danger should in any case be assessed as carefully as possible while assuming, at most, that all micropollutants may come into direct contact with man through the various potential pathways throughout their entire lifetime, regardless of the factors that reduce their presence.